Coalition Formation with Border Carbon Adjustment - Mark Schopf (ZBW - Leibniz Information Centre for Economics, 2020)
The present paper analyzes the impact of a climate coalition's border carbon adjustment on emissions from commodity production, welfare and the coalition size. The coalition implements border carbon adjustment to reduce carbon leakage and to improve its terms of trade, while the fringe abstains from any trade policy. With symmetric countries, the optimal import tax or export subsidy is positive but smaller than the coalition's implicit emission price. With a linear-quadratic specification, the coalition exports the commodity. Total emissions decrease with the coalition size, and total welfare increases [decreases] with the coalition size if the coalition is large [small]. Then, the reduced climate costs outweigh [are outweighed by] the increased trade distortions. The unique stable coalition consists of three or more countries, including the grand coalition, and raises the welfare of each country compared to the business-as-usual equilibrium. If no [each] country implements a trade policy, the stable coalition consists of two [three] or less countries. Compared to the case in which only the coalition implements border carbon adjustment, the welfare of each country is reduced [if the stable coalition then consists of four or more countries]. All results are derived analytically.
Keywords: F13; F18; H23; Q54; Q56; Q58; 330; Carbon Leakage; Climate Change; Environmental Policy; Nash Equilibrium; Terms of Trade